Erythrocyte micronucleus cytome assay in Passer domesticus and environmental remote sensing for inferring the quality of wild, rural, and urban areas - Mendez, Sofía Elena (2022)
The study of biomarkers in free-living birds can help to indicate the degree of contamination in distinct environments. In addition, these environments can be characterized through the information provided by satellite images. The objectives of the present study were to analyze the types and quantity of cytogenetic biomarkers in Passer domesticus (House sparrow) from three different environments, wild, rural, and urban, and to analyze them in the context of land use and anthropogenic actions. Five thousand erythrocytes per bird were analyzed for the following nuclear alterations (NA): micronuclei (MN), nuclear buds, notched nuclei, binucleated cells, nucleoplasmic bridges, nuclear tails, peripheral nuclei, and anucleated cells. In the study, wild birds exhibited five types of NA, seven types were found in rural birds, and all types were encountered in urban birds. The only NA that exceeded a frequency of 2 NA/1000 erythrocytes were peripheral nuclei in birds from the rural and urban sites, the latter environment characterized by 87% urban soil and air pollution. The highest frequencies of MN, peripheral nuclei, and anucleated erythrocytes were recorded in sparrows from the rural site (p ≤ 0.05). This area had been sprayed with chlorpyrifos 48%, the most widely used organophosphate in the region. Sparrows from the wild site, made up of 100% native forest, had higher frequencies of notched nuclei (p ≤ 0.05). A precedent is set for the use of environmental remote sensing in a complementary manner with cytogenetic biomarker studies in birds for a joint analysis in environmental assessment.